Species diversity, distribution and status of fishes in Chitwan district and adjacent areas, Nepal - Jha, Dilip Kumar (Journal of Natural History Museum, 2018)
Chitwan district is endowed with varied aquatic resources which harbor diverse fish species in central Nepal. A total of 111 fish species were collected from different sampling sites of several tributaries of Trisuli, Rapti and Narayani river systems in Chitwan district and adjacent areas from August 2011 to July 2016. These species belong to 9 orders, 27 families and 72genera. Among the orders, Cypriniformes had the highest number of species (49%) followed by Siluriformes (30%), Perciformes (12%), Synbranchiformes (3%), Osteoglossiformes (2%) while Anguiliformes, Beloniformes, Clupeiformes and Tetraodontiformes represented each by about 1%. Cyprinidae has the highest number of species (40%) among the families followed by Sisoridae (12%), Bagridae (7%), Cobitidae (5.4%), Schilbeidae (4.5%), Channidae (3.6%), Balitoridae (2.7%), Mastacembelidae (2.7%), Siluridae (2.7%), Notopteridae (1.8%), Ambassidae (1.8%), Nandidae (1.8%) and Mugilidae (1.8%). Other families accounted forabout 1% were Anguillidae, Belonidae, Clupeidae, Psilorhynchidae, Anabantidae, Gobiidae, Belontidae, Synbranchidae, Amblycipitidae, Pangasidae, Clariidae, Heteropneustidae, Chacidae and Tetraodontidae. The Botia geto was reported for the first time from Rapti river of Chitwan and adjacent area. Different fish species are naturally maintained in aquatic systems and support livelihoods of the people. Catches of major food fishes are declining due to overexploitation of resources, therefore, appropriate measures are needed at once to maintain and conserve the indigenous stock.